2020
DOI: 10.2147/vhrm.s279028
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolite Profiling of Osteoporosis and Atherosclerosis in Postmenopausal Women: A Cross-Sectional Study</p>

Abstract: Purpose: Atherosclerosis (AS) and osteoporosis (OP) are common causes of morbidity and mortality in postmenopausal women and are connected via an unknown mechanistic link. Metabolite profiling of blood samples may allow the identification of new biomarkers and pathways for this enigmatic association. Patients and Methods: We studied the difference in 148 metabolite levels from serum samples in postmenopausal women with AS and OP compared with those in healthy participants in this cross-sectional study. Quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…After acute myocardial infarction, the lower circulating lysine provides other evidence supporting our results 28,29 . The assessment of serum levels of metabolites from postmenopausal women with atherosclerosis and osteoporosis compared with healthy participants showed apparent differences in amino acid profile 13 …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…After acute myocardial infarction, the lower circulating lysine provides other evidence supporting our results 28,29 . The assessment of serum levels of metabolites from postmenopausal women with atherosclerosis and osteoporosis compared with healthy participants showed apparent differences in amino acid profile 13 …”
Section: Discussionsupporting
confidence: 80%
“…There is no sharing of metabolite profile between us and Värri et al's 13 study, possibly related to the alteration of metabolites in postmenopausal osteoporosis and the simultaneous occurrence with atherosclerosis In Floegel's 44 study, none of the metabolites, such as acylcarnitines and amino acids, were associated with the risk of myocardial infarction in healthy adults.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Previous studies showed lower acetate concentrations in postmenopausal women with carotid artery calcification [47] and in myocardial ischemia patients without stenosis [48] compared to controls.…”
Section: Acetate Cardiovascular Risk and Vascular Healthmentioning
confidence: 86%